ON TECHNIQUE OF FUZZY EXPERT KNOWLEDGE REPRESENTATION - Lyudmila Victorovna Borisova; Valery Petrovich Dimitrov; Inna Nikolayevna Nurutdinova (Advanced Engineering Research, 2014)
Some aspects of representing the fuzzy expert knowledge in the decision-making problems on the process machine adjustment are considered. The technique based on the use of different criteria of consistency in the representation of fuzzy knowledge which includes considering various expertise hierarchy is offered. This technique allows determining a rational term set of the linguistic variable for the construction of the generic membership functions under the input and output system parameters specification. The improved background for choosing terms of the linguistic variables allows optimizing the KB parameters based on the fuzzy production rules. The technique is applied in the subject domain of “Grains combining”; several input linguistic variables are considered; fuzzy knowledgebase creation phases are exemplified by them; models consistency indices are calculated; optimum term sets of each of the variables are selected; generic membership function parameters are obtained.